Mundialização no cinema da retomada: hibridação cultural e antropofagia como enunciação da identidade e alteridade. - Eduardo Dias Fonseca (2012)
The constant and rapid changes in the contemporary world generate movements related to the globalization of the economies that operate in the world in a relational manner with the movements of culture. Hybridism, fueled by greater interpenetration of cultures, takes global levels redimensioning national narratives. The cycle of Cinema da Retomada, that took place in Brazil during the 1990s, has characteristics of the mondialisation of culture that are connected to the transnational narratives. The fall of Embrafilme and the new legal apparatus (Lei do Audiovisual), establish a new phase in the film production in Brazil. When analyzing films such as Carlota Joaquina, a princesa do Brazil (1995), directed by Carla Camurati; Terra Estrangeira (1995), directed by Walter Salles and Daniela Thomas; Como nascem os anjos (1996), directed by Murilo Salles; Baile Perfumado (1997), directed by Lírio Ferreira and Paulo Caldas; Hans Staden (1999) directed by Luis Alberto Pereira, and Cronicamente Inviável (1999), directed by Sérgio Bianchi, it is possible to find aspects of the interpenetration of the becoming world in the becoming Brazil and vice versa. The observing of the different moments of the Brazilian Cinema and the Antropofagia movement led by Oswald de Andrade during the 1920´s, both seen as cultural asset of the nation, could be found in negotiation with the films produced during the Cinema da Retomada.